Product Development Strategy and Financial Management at Turbo Sakti MSME in Increasing Competitiveness in the Cassava and Corn Chips Industry - Hermanto, Bambang; Buchari, Ach; Novianty, Devina Aulia; Nurhayani, Fifin; Amaliya Putri, Dwi Rosa; Faruq, Moh. Umarul; Okfandi A.S, Yusta; Ihsan Arisandi, Muhammad Nurul (Edumedia Solution, 2025)
Turbo Sakti Cassava Chips is a micro, small, and medium enterprise (MSME) located in Manding and engaged in the production and marketing of traditional cassava-based snack products. Amidst increasing competition in the local snack industry, this study focuses on analyzing the business development strategies and financial management practices implemented by Turbo Sakti to increase its competitiveness. This study uses a qualitative descriptive method with data collection techniques through direct interviews with the owner, field observations, and documentation studies to gain a comprehensive understanding of the MSME's operations. The results show that Turbo Sakti has implemented various strategies to encourage business growth. These strategies include continuous product innovation, particularly in developing flavor variations to suit consumer tastes, investing in modern and environmentally friendly packaging, and utilizing digital media such as social media to expand market reach. In addition, this business also builds brand identity and customer loyalty through consistent quality and active participation in local community activities.